Educational Quality Improvement Events Based on Exhibition Materials in Practical Training Lessons (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article talks about ways to improve the quality of education by using the Venn diagram in the organization of practical training. It is based on the fact that by using this method in all departments of theoretical mechanics, which are part of the group of technical sciences, it is possible to achieve the desired result based on demonstration in students' mastery of basic words and phrases related to science.